TIMP-1-expressing breast tumor spheroids for the evaluation of drug penetration and efficacy - Bae, In yeong; Wooshik Choi; Oh, Seung Ja; Kim, Chansoo; Kim, Sang-Heon (Wiley | American Institute of Chemical Engineers; Society for Biological Engineering, 2022)
Abundance of stromal cells and extracellular matrix (ECM) is observed in breast cancer, acting as a barrier for drug penetration and presenting a key issue for developing efficient therapeutics. In this study, we aimed to develop a three-dimensional (3D) multicellular tumor model comprising cancer and stromal cells that could effectively mimic the drug resistance properties of breast cancer. Three different types of spheroid models were designed by co-culturing breast cancer cells (MDA-MB-231) with three different types of stromal cells: human adipose-derived stromal cells (hASCs), human bone marrow stromal cells, or human dermal fibroblasts. Compared with other models, in the hASC co-culture model, tissue inhibitor of metalloproteinases-1 (TIMP-1) was highly expressed and the activity of matrix metalloproteinases was decreased, resulting in a higher ECM deposition on the spheroid surfaces. This spheroid model showed less drug penetration and treatment efficacy than the other models. TIMP-1 silencing in hASCs reduced ECM protein expression and increased drug penetration and vulnerability. A quantitative structure-activity relationship study using multiple linear regression drew linear relationships between the chemical properties of drugs and experimentally determined permeability values. Drugs that did not match the drug-likeness rules exhibited lower permeability in the 3D tumor model. Taken together, our findings indicate that this 3D multicellular tumor model may be used as a reliable platform for efficiently screening therapeutics agents for solid tumors.